Weak formulation study for thermoelastic buckling analysis of thick laminated cylindrical shells - Ding, Kewei (Zielona Góra: Uniwersytet Zielonogórski)
Weak formulations of mixed state equations of closed laminated cylindrical shells are presented in the Hamilton System. The Hamilton canonical equation of closed cylindrical shell is established. By means of applying the transfer matrix method and taking the advantage of Hamiltonian matrix in the calculation, a unified approach and three-dimensional thermoelastic solutions are obtained for the buckling analysis of closed thick laminated cylindrical shells.
Keywords: weak formulations; buckling analysis; laminated cylindrical shells; thermoelastic; Hamilton canonical equation